Implementation of Online Learning on the Understanding of Elementary Schools Students: Implementasi Pembelajaran Daring pada Pemahaman Siswa di Sekolah Dasar - Firmayanti, Roisa; Uddin, Moch.Bahak (Indonesian Journal of Education Methods Development, 2021)
This study aims to find out what the implementation of online learning is like at SDI Ma'arif Bandulan and to find out the benchmarks for understanding grade VI students at SDI Ma'arif Bandulan. In this study using descriptive qualitative research. The findings of the data found at SDI Ma'arif Bandulan in the implementation of online learning are that all teachers have applied their online learning method synronically, namely using WA-based applications as media that help the learning process and its implementation. From the results of the Implementation of Online Learning on the understanding of grade VI students, everything is complete.